Alkaline aluminosilicate binder-based adhesives with increased fire resistance for structural timber elements - Krivenko, P. V.; Guzii, S. G.; Bondarenko, O. P. (My University, 2019)
The paper presents data on the use of the alkaline aluminosilicate binder-based adhesive of the system Na2O•Al2O3•(4-6)SiO2•(17-20)H2O for gluing and fire protection of structural timber elements. The results of the study of thermoresistant phases in the reaction products of the alkaline aluminosilicates are reported and discussed. The results allowed to show that at SiO2/Al2O3 between 5 and 6 the zeolite-like phases of heulandite types, which, under action of temperatures, are able to form a porous aluminosilicate artificial stone with low thermal conductivity (λ=0.09 Wt/m⋅К, DSTU B V.2.7-105-2000 (GOST 7076-99)) are formed in the reaction products. The use of the developed aluminosilicate adhesives allow for to classify the structural timber elements as hardly burnable and hardly flammable materials (GOST 12.1.044-1989, EN 13823 + A1: 2014-12, ASTM E119-07). They have the following characteristics: water resistance D3 (EN 204:2001), resistance in splitting up 7.8 MPa (GOST 16483.5-1973), adhesion in normal pull-off test up to 2.6 MPa (GOST 32299- 2013 (ISO 4624:2002)).
Keywords: adhesion; alkaline aluminosilicate binders; adhesives; hardly burnable; hardly flammable; strength in splitting; heat conductivity; timber; zeolite-like phases